Necrotising granulomata in prostatic resection specimens--a sequel to previous operation. Issue 9 (September 1983) - Lee, G; Shepherd, N
Abstract : Six cases, in which necrotising granulomata were discovered in transurethral resection specimens of prostate gland, are described. In four of these cases, granulomata of foreign body type were also present. None of the patients had clinical, microbiological or histological evidence of tuberculosis, past or present. All had had at least one previous prostatectomy. The necrotising granulomata had characteristic microscopic appearances. They were almost certainly caused by operative trauma.